Use of synthetic peptides to map the antigenic determinants of glycoprotein D of herpes simplex virus. - Strynadka, N C (1988)
The predictive algorithm Surfaceplot (J.M.R. Parker, D. Guo, and R.S. Hodges, Biochemistry 25:5425-5432, 1986) was used to examine glycoprotein D of herpes simplex virus type 1 (HSV-1) for amino acid residues with a high probability of being exposed on the molecular surface. Based on these data, 11 different peptides corresponding to 10-residue segments in the primary sequence of glycoprotein D and one 20-residue segment were synthesized, conjugated to carrier proteins, and used to generate specific antisera in rabbits. Two synthetic peptides predicted not to be on the surface of glycoprotein D were included as negative controls. The polyclonal antisera against individual synthetic peptide conjugates were in turn evaluated for their ability to recognize both isolated glycoprotein D and intact HSV-1 virions in an enzyme-linked immunosorbent assay. Based on Surfaceplot predictions, eight linear antigenic sites on glycoprotein D were thereby defined from the 12 antipeptide antisera prepared. Four of these sites contained epitopes to which complement-independent neutralizing antibodies could be generated. The latter sites corresponded to sequences 12 to 21, 267 to 276, 288 to 297, and 314 to 323 of the mature protein. An additional peptide sequence, 2 to 21, was found to generate antisera which had potent virus-neutralizing capacity in the presence of complement. Identification of a neutralizing epitope in the sequence 314 to 323 makes it likely that the membrane-spanning region of glycoprotein D is within the subsequent sequence, 323 to 339. Antipeptide antisera prepared in this study from 12 synthetic peptides contained 13 surface sites predicted by Surfaceplot, of which 7 were not predicted by the parameters of Hopp and Woods (Proc. Natl. Acad. Sci. USA 78:3824-3828, 1981). Of these seven sites not predicted by the Hopp and Woods plot, all generated antipeptide antibodies that bound to HSV-1 virions and three of these seven sites generated neutralizing antibodies. In total, 8 of 12 synthetic peptides containing surface regions produced antipeptide antibodies that bound to HSV-1 virions and 5 of these generated neutralizing antibodies. These results suggest the advantages of Surfaceplot in mapping antigenic determinants in proteins.